INTERNET ETHICS AND INTERNET ETHICS IN THE INFORMATION SOCIETY - Shahlo Muhammadaliyevna Askarova (Galaxy International Interdisciplinary Research Journal, 2023)
This is it in the article ethics and internet ethics in other words , from the Internet fruitful use of the Internet useful and harmful sides , information society concept from the internet use young generation to the psyche effect as well instructions about the word held .